PERISTILAHAN BELADIRI OTAR-OTAR MASYARAKAT MELAYU SAMBAS - Nonik, Nonik; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The research about describe the term, the component of meaning, the meaning of lexical and the meaning of culture in otar-otar martial art in form of movement, instruments music instrument and kuntau movement. The method that was used was observation method, interview, documentation, and descriptive. Based on the data analysis, otar-otar martial art there are some data which is rasists of is data for the terminology of otar-otar movement 4 data the terminology of instrument in otar-otar martial art, 4 data for terminology of otar-otar martial art music instrument, and 7 data for terminology of kuntau in otar-otar martial art. Result of data analysis of based on data analysis result of the meaning component that has been done and it was found that the meaning component of the otar-otar martial art movement there were 4 terminology data, the music instrument of otar-otar martial art there were 4 terminology data, and kuntau martial art movement there were 7 terminology data. The result of interview that was obtained, it means there were 6 cultural meaning in otar-otar martial art. It was 5 for otar-otar martial art movement and it was 1 for the instrument of otar-otar martial art. Keywords: terminology, martial art, otar-otar, kuntau, Sambas Malay.